2007
DOI: 10.1017/s0950268807009806
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies against Rift Valley fever virus in Kenyan wildlife

Abstract: Rift Valley fever virus (RVFV) is an arbovirus associated with periodic outbreaks, mostly on the African continent, of febrile disease accompanied by abortion in livestock, and a severe, fatal haemorrhagic syndrome in humans. However, the maintenance of the virus during the inter-epidemic period (IEP) when there is low or no disease activity detected in livestock or humans has not been determined. This study report prevalence of RVFV-neutralizing antibodies in sera (n=896) collected from 16 Kenyan wildlife spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
144
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(153 citation statements)
references
References 26 publications
6
144
2
1
Order By: Relevance
“…A high seroprevalence in buffaloes has been demonstrated by many researchers mainly in sub-Saharan Africa especially in South Africa [59,60] and Kenya [61]. In our study, seroprevalence was also high.…”
Section: Discussionsupporting
confidence: 73%
“…A high seroprevalence in buffaloes has been demonstrated by many researchers mainly in sub-Saharan Africa especially in South Africa [59,60] and Kenya [61]. In our study, seroprevalence was also high.…”
Section: Discussionsupporting
confidence: 73%
“…12,13 Overall, in our Kruger National Park sample, seropositivity was highest in the first year of study (2000)(2001), likely secondary to anomalous heavy rainfall that had occurred in 2000 ( Figure 5 ). Transmission of RVFV is associated with excessive rainfall in high-risk areas because of the abrupt increase in mosquito numbers after flooding events.…”
Section: Discussionmentioning
confidence: 84%
“…3 Many wild animals have been shown to be seropositive for RVFV-neutralizing antibodies during IEP, including African buffalo, black rhino, lesser kudu, impala, African elephant, kongoni, and waterbuck. 12 Of interest, the highest wild animal RVFV antibody prevalence (> 15%) was observed in black rhinos and among ruminants (kudu, impala, African buffalo, and waterbuck) and the highest hemagglutination-inhibition titers (≤ 1:1,280) were observed primarily in buffalo, including young animals born after known epizootics, i.e., during the IEP. 12 African buffalo ( Syncerus caffer ) and Asian water buffalo ( Bubalus bubalis ) have been found to have high RVFV seroprevalence in other cross-sectional surveillance studies in Africa, and it has been suggested that they may serve as one of the amplifying hosts for RVFV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This flooding displaced entire villages and became breeding grounds for vector species. Infected Aedes transmit RVF to a variety of livestock and wildlife, which may develop high and sustained viremia, 29 and directly to humans; when virus levels in bloodstream are high, RVF may then be transmitted to other animals or to humans by other mosquitoes, and theoretically by any biting or blood-sucking insect. It appears that heavy rains and flooding preceded advent of outbreaks by at least 1 month in each of the affected areas.…”
Section: Discussionmentioning
confidence: 99%